Research of the Attractiveness Factors of Tactical Competitive Shooting Mobile Games Based on Evaluation Grid Method - Qi Shen; Chun-Chih Chen; Shu-Ming Wu (E3S Web of Conferences, 2020)
The purpose of this paper is to explore the game player’s experience and preference for tactical competitive shooting mobile games, and to identify the attractiveness quality factors that affect the tactical competitive shooting mobile game design. In this paper, Game For Peace is the subject of discussion and research; qualitative research methods are adopted to go deeper into interviews involving deeper gamers; the attractiveness of the tactical competitive shooting mobile game is summarized; the evaluation grid is constructed and analyzed, which provides a reference for the subsequent tactical competitive shooting mobile game design and improvement.